A visual analysis: 3D computer graphic with narrative structure of adhan recitation / Lili Eliana Mohd Radzuana...[et.al] - Mohd Radzuana, Lili Eliana; Shamsudin, Wan Nur Khalisah; Abd Razak, Mohamed Razeef; Harun, Azahar (2016)
In recent years, a number of researchers have reported that there has been an increasing interest in incorporating three dimensional computer graphics (3D CG) features in various applications from different areas. In the broadcasting industry, the growing demand to produce a TV content which integrates the 3D CG elements leads to a further improvement of the product. Designers need to identify creative approaches to present the content creatively and meaningfully. Narrative structured content that uses 3D CG as the visual signs are expected to be acceptable by the audience due to its characteristics that able to engage them emotionally and encourage their perceptive abilities. However, the narrative structure should be able to represent the designated content effectively in order to offer novel experience to the viewers. This study seeks to find the relations of visual signs that use 3D CG with the narrative structured designed for the adhan recitation on TV network. Qualitative interpretative approach is used to find the latent meaning of the visual signs. Since the adhan recitation in local TV networks has never been created using entirely 3D CG features, most likely it will acquire significant reaction by the viewers both emotionally and perceptively.